Study of endometrial histopathology in women with abnormal uterine bleeding - Gopalan, Ushadevi; Rajendiran, Sathiyakala; Ranganathan, Karnaboopathy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Abnormal uterine bleeding is a major gynaecological problem accounting for 33% of Gynaec outpatients. The cause of the bleeding is established in only 50-60% of the cases. The aim of this study was to evaluate the various histopathological patterns in the endometrial biopsy of patients presenting with abnormal uterine bleeding and to determine the specific pathology in the different age groups. Methods: This was a prospective study done in a tertiary care teaching hospital for a period of 2 years. Total of 905 patients with abnormal uterine bleeding were included in the study and they were subjected to a Dilatation and Curettage. Histopathological examination of the endometrial biopsy was done and the various histopathological patterns identified and classified. Results: The age of patients ranged from 24-74 years. 54.7% were in the age group 40-49 years followed by 23.4% in the age group 30-39 years. The most frequent findings were proliferative findings in 47.3% followed by secretory endometrium in 16.1 % patients. Proliferative endometrium was more common in the age group 40-49 years as also disordered proliferation, secretory endometrium, cystoglandular hyperplasia and endometrial hyperplasia. Conclusions: Endometrial curettings and biopsy is an important diagnostic procedure for assessing all cases of abnormal uterine bleeding and to plan for successful management.